Awareness of Cervical Cancer Screening Amongst Pakistani Medical Students and Doctors; A Systematic Review - Mohammad Mustafa Farooq Khan, Muhammad Talha Mumtaz, Amman Afreen, Maliha Aslam Khan, Khizar Ali Chaudhary, Muhammad Uzair, (Pakistan Journal of Medical & Health Sciences, 2023)
Background Cervical cancer screening is one of the most important public health interventions for cervical cancer prevention, yet awareness among Pakistani medical students and doctors is alarmingly low. Objective: to provide an in-depth understanding of the awareness and attitudes of Pakistani medical students and doctors towards cervical cancer screening Methodology: A systematic review of the literature was conducted, and qualitative and quantitative findings from studies conducted between January 2010 and June 2022 were synthesized. Results: The research found that Pakistani medical students and doctors have limited knowledge of cervical cancer and cervical cancer screening and a generally negative attitude towards cervical cancer screening. The paper also identified numerous influencing factors that contribute to the low awareness and attitudes towards the screening, such as traditional cultural beliefs, lack of training and education, and limited access to health care services. Conclusion, the research found a desperate need for interventions to raise awareness and to create an environment of acceptance and support for cervical cancer screening among Pakistani medical students and doctors. Keywords: Cervical Cancer, Screening, Pakistani Medical Students and Doctors, Knowledge, Pap smear, Human Papilloma Virus (HPV)